2019
DOI: 10.5755/j01.mech.25.5.22689
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Numerical Investigation of the Effect of Different Temperature and Deformation Speeds on Mechanical Properties and Springback behaviour in Al-Zn-Mg-Cu Alloy

Abstract: Thanks to their low density and high strength, the 7XXX series aluminum alloys are widely used as a support/beam parts in the aerospace industry. This alloy is target in the lightening studies of the automotive industry and surveys for sheet metal are still in progress. It is a series of alloys that can be applied to the aging process and has the most effect on mechanical properties. As formability is quite weak, methods are investigated. In this study, tensile test, bending test and Erichsen tests are perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
0
1
0
2
Order By: Relevance
“…Aynı zamanda, ABAQUS programında bu modeli uygulamışlar ve yüksek sıcaklıklarda uygulanabilir olduğunu vurgulamışlardır. 7075 alüminyum alaşımında farklı sıcaklık ve deformasyon hızının mekanik özelliklere etkisi incelenen diğer çalışmalarda da (Puchi-Cabrera et al , 2011;Lu et al , 2018;Xiao et al , 2018;Kilic, 2019), sıcaklık artışıyla birlikte akma mukavemeti düşerken, sünekliğin arttığı görülmüştür (Şekil 13-14). Deformasyon hızının artışıyla akma ve çekme mukavemeti artarken, sünekliğin pek fazla değişmediği gösterilmiştir.…”
Section: Umagd (2022) 14(2) 406-419 Kılıç and Demirdöğenunclassified
See 1 more Smart Citation
“…Aynı zamanda, ABAQUS programında bu modeli uygulamışlar ve yüksek sıcaklıklarda uygulanabilir olduğunu vurgulamışlardır. 7075 alüminyum alaşımında farklı sıcaklık ve deformasyon hızının mekanik özelliklere etkisi incelenen diğer çalışmalarda da (Puchi-Cabrera et al , 2011;Lu et al , 2018;Xiao et al , 2018;Kilic, 2019), sıcaklık artışıyla birlikte akma mukavemeti düşerken, sünekliğin arttığı görülmüştür (Şekil 13-14). Deformasyon hızının artışıyla akma ve çekme mukavemeti artarken, sünekliğin pek fazla değişmediği gösterilmiştir.…”
Section: Umagd (2022) 14(2) 406-419 Kılıç and Demirdöğenunclassified
“…Fakat alüminyum alaşımlarına plastik şekil verme işleminde çeşitli sorunlarla karşılaşılmaktadır. Plastik şekil verme yeteneğini geliştirmek üzere sıcaklık arttırılarak deneysel çalışmalar yapılmaktadır (Kilic, 2019;Liu et al , 2020;Simonetto et al , 2020;Attar et al , 2021).…”
Section: Introductionunclassified
“…MG Lee et al [7] derived and implemented a practical two-surface plasticity model based on classical Dafalias/Popov and Krieg concepts to incorporate yield anisotropy and three hardening effects for nonmonotonous deformation paths: the Bauschinger effect, transient hardening and permanent softening. And they proposed and implemented a simple-but-effective stress-update scheme avoiding overshooting [8]. They found that two-surface model improved such predictions significantly as compared with single-surface models, while the differences between two-surface simulations and experiments were insignificant.…”
Section: Introductionmentioning
confidence: 99%